2022
DOI: 10.5812/jjnpp-130785
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Properties of Natural Postbiotics Derived from Five Lactic Acid Bacteria

Abstract: Background: The application of natural antimicrobial and antioxidant agents in food and pharmaceutical products has recently become a trend due to the high demand for them from consumers. Postbiotics are bioactive compounds that are produced when the healthy bacteria in the gut ferment fiber. Objectives: This study aimed to compare the antibacterial and antioxidant properties of postbiotics from 5 different lactic acid bacteria (LAB) including Lactiplantibacillus fermentum, Lactiplantibacillus plantarum, Lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Probiotic bacteria produce antimicrobial compounds such as organic acids and bacteriocins [26]. Contrary to our results, Noori et al, [13] found that L. acidophilus and L. plantarum were unable to eliminate the pathogenic bacteria; however, L. casei and L. rhamnosus postbiotics exhibited excellent antimicrobial activity. Magnusson et al, [27] reported that the antimicrobial activity L. plantarum depends on bacteriocins, organic acids and other inhibitory substances.…”
Section: Antimicrobial Activitycontrasting
confidence: 99%
See 1 more Smart Citation
“…Probiotic bacteria produce antimicrobial compounds such as organic acids and bacteriocins [26]. Contrary to our results, Noori et al, [13] found that L. acidophilus and L. plantarum were unable to eliminate the pathogenic bacteria; however, L. casei and L. rhamnosus postbiotics exhibited excellent antimicrobial activity. Magnusson et al, [27] reported that the antimicrobial activity L. plantarum depends on bacteriocins, organic acids and other inhibitory substances.…”
Section: Antimicrobial Activitycontrasting
confidence: 99%
“…Moradi et al [12] mentioned that postbiotics are more resistant to food processing and they can remain active for longer periods. Noori et al [13] found that massive amounts of postbiotics were applied in the food industry to produce functional foods. In general, postbiotics have shown all the bene cial effects of probiotics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The role of different periodontopathogens, such as A. actinomycetemcomitans , in chronic and progressive periodontitis has been proven in previous studies ( 16 , 17 ). Due to the protective role of probiotics ( 18 , 19 ), the current study aimed to mark a novel investigation by comparatively examining both the antioxidant activity and the antimicrobial effect of mentioned LCFSs (i.e., L. acidophilus , L. casei , and L. paracasei ) against the oral bacteria (i.e., A. actinomycetemcomitans and S. mutans ) and the effects on the cell proliferation and migration of PDLSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, cell-free supernatant (CFS), a solution that contains metabolites produced as a result of microbial growth, represents an invaluable metabolite-rich source. For instance, the antioxidant, antimicrobial, and anticancer properties of CFS have been demonstrated [142][143][144]. In 2016, An and Ha showed that the expression of particular CSC markers, CD44, CD133, CD166, and ALDH1, can be inhibited by Lactobacillus plantarum (LP) supernatant.…”
Section: Microbiota-derived Metabolites With Activity Towards Cscsmentioning
confidence: 99%